Novel Artificial Biofilm Equivalent for Denture Surfaces: A Pilot Study. (27th January 2022) - Kunze, Jan-Philipp; Boening, Klaus; Meissner, Heike; Kresse-Walczak, Katarzyna
Abstract : The microbial population of the dental biofilm is embedded in an extracellular matrix that contains organic polymers such as polysaccharides. The extracellular matrix promotes biofilm adhesion on surfaces of dental prostheses and acts as a protective barrier. Thus, a breakdown of the extracellular matrix is crucial for an effective mechanical biofilm removal by brushing. The purpose of this study was to develop an artificial biofilm equivalent (ABE) that is able to mimic the mechanical properties of a natural biofilm concerning abrasion resistance. It contains the two polysaccharides chitosan (ChS) and methylcellulose (MC). Polymethylmethacrylate (PMMA) cylinders (n = 80 ) were manufactured and coated with the ABE with varying concentration ratios of ChS and MC. Eight test series (n = 8 each) with different mixing ratios of ChS/MC were tested for their abrasion resistance to brushing in a toothbrush simulator. For the ABE, a total of 2.0 g of polysaccharides were added to 100 ml of 2% acetic acid: 0.3–1.0 g ChS and 1.0–1.7 MC, respectively. Furthermore, two control series (n = 8 each) with 2.0 g of ChS only or 2.0 g of MC only were performed. Coated specimens were subjected to an increasing number of brushing strokes from 5 to 45 via abrasion test. The specimens were photographed, and a computerized planimetric method (CPM) was used to calculate the percentage of remaining ABE on the brushed areas of the PMMA cylinders. The abrasion resistance of the ABE to brushing decreased with an increasing ratio of MC in the mixture. The abrasion resistance of the ABE can be adjusted by changing the ratio of ChS and MC.